Electrohydrodynamic drying of multiple food products: Evaluating the potential of emitter-collector electrode configurations for upscaling. (January 2019) - Defraeye, Thijs; Martynenko, A.
Abstract: Electrohydrodynamic (EHD) drying is a promising, non-thermal drying technology, based on ionic wind generation between an emitter and a collector electrode. This simulation-based study evaluates impact of various emitter-collector configurations for EHD drying in order to assess their potential towards industrial upscaling. The conventional wire-to-plate configuration, which creates impinging flow, is found not to be an optimal solution for EHD drying of multiple food products in a fast and uniform way. With a single wire (emitter), it is found that the products placed more downstream dry slower due to the progressive loading of the air with water vapor. With multiple emitters, up to a threefold increase in drying time of the food products is found, compared to a single wire. This increase is caused by the recirculation of most air. To avoid water vapor accumulation in the drying zone, a wire-to-mesh configuration is proposed. The mesh collector minimizes interference of neighboring airflows and avoids recirculation of moist air in the drying zone. As such, the wire-to mesh configuration provides more uniform drying between adjacent products, but also within a product, as it can dry from all its surfaces. An increase in emitter density for the wire-to-mesh configuration leads to an overall increase in air speed, but, surprisingly, not to increased product drying rates. The reason is that the high-speed EHD airflow is always generated very locally in the vicinity of the emitter and collector. Thereby the convective drying process is not affected so much by the emitter density. Highlights: The upscaling potential of various emitter-collector configurations is evaluated. Wire-to-plate configuration is not preferred for EHD drying of multiple food products. A mesh collector minimizes interference of neighboring airflows. Wire-to mesh configuration provides more uniform drying between adjacent products.